2019
DOI: 10.1038/s41416-019-0456-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel NPM1-RARG-NPM1 chimeric fusion in acute myeloid leukaemia resembling acute promyelocytic leukaemia but resistant to all-trans retinoic acid and arsenic trioxide

Abstract: The RARG gene is a member of the nuclear hormone receptor superfamily and shares high homology with RARA and RARB. RARA is involved in translocation with PML in acute promyelocytic leukaemia (APL). Little is known about RARB or RARG rearrangement. RARG fusions were reported in only five APL patients and the partner genes were NUP98, PML and CPSF6. Here, we report NPM1 as a new partner gene of RARG and identify a unique NPM1-RARG-NPM1 chimeric fusion for the first time in an old male with morphological and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…The NPM1 gene, already reported as a translocation partner of RARA, was also recently identified as a fusion partner of RARG [86]. Multiplex reverse transcription polymerase chain reaction (RT-PCR) and whole genome sequencing revealed insertion of RARG (5'UTR-exon9) within the NPM1 gene to yield NPM1-RARG-NPM1 chimeric proteins.…”
Section: The Npm1-rarg-npm1 (Karyotype Non-determined)mentioning
confidence: 99%
“…The NPM1 gene, already reported as a translocation partner of RARA, was also recently identified as a fusion partner of RARG [86]. Multiplex reverse transcription polymerase chain reaction (RT-PCR) and whole genome sequencing revealed insertion of RARG (5'UTR-exon9) within the NPM1 gene to yield NPM1-RARG-NPM1 chimeric proteins.…”
Section: The Npm1-rarg-npm1 (Karyotype Non-determined)mentioning
confidence: 99%
“…Mutational hotspots or whole coding regions of 58 genes that are known to mutate frequently in hematologic malignancies were sequenced using a targeted, multiplexed, amplicon-based high-throughput sequencing protocol as previously reported [6]. [7,8]. The two superenhancers (SEs) that have been annotated in the SEdb, with potential blood-cell specific functions within the genomic region of ETV6, were SE_00_00600344 (chr12:11898032-11928354), which spans ETV6 exon 2, and SE_02_25500737 (chr12:11986329-12016687), which spans ETV6 exon 3 [9].…”
Section: High-throughput Sequencing (Hts) Mutation Screeningmentioning
confidence: 99%
“…Further study demonstrated that the NPM1-RARG-NPM1 fusion leads to both impairment of the NPM1 protein and abnormal RARG, which contributes to impaired differentiation and leukogenesis. 71 To investigate the correlation of NPM1 mutation with clinical features and biological characteristics, the NPM1 mutation was analyzed in bone marrow cells from 173 consecutive patients with de novo AML. 12 The results revealed a remarkable difference in the incidence of NPM1 mutation between adult and pediatric patients.…”
Section: Npm1 Mutations In Amlmentioning
confidence: 99%